الفخامة والإفراط التزييني في الصور الشخصية لملوك القاجار بالفن الإسلامي - العبيد، حنان بنت ابراهيم بن عبدالله (دار سمات للدراسات والأبحاث, 2018)
يعد فن التصوير أحد الفنون المزدهرة في الحضارة الإسلامية، وقد تأثر الفن الإسلامي إلى حد كبير بفن وثقافة أوروبا خلال فترة حكم القاجار. وفن الصور الشخصية في عهد ملوك القاجار انحصر في نطاق البلاط الملكي، نتيجة لانفتاح ملوك القاجار على الغرب، حيث أظهر الفنانون في هذا العصر رغبة متزايدة لاستيعاب الفنون الأوروبية لمواءمة متطلبات الجمال الجديدة. وقد اتخذ ملوك القاجار الصورة وسيلة للتعبير عن القوة والنفوذ سواء داخل البلاط أو خارجه، بالإضافة إلي استخدامها كأداة لها أهداف وغايات سياسية، ووسيلة لإبراز السلطة والثروة. وقد كانت معظم الصور الشخصية لملوك القاجار انعكاسا لأحوال المجتمع القاجاري، واتجاهه نحو الاستمتاع بمباهج الحياة، واتسام حياتهم بصفة خاصة بالثراء، واستغلال بعضهم إمكانات الفن، بخاصة الصور الشخصية، في التأثير والإبهار. وقد بالغ فنانو ملوك القاجار وبإفراط، في تصوير الملابس والعمائم والأثاث والأسلحة المزينة بالمجوهرات في الصور الشخصية، لإظهار الفخامة. وقد اتخذت الدراسة الحالية قراءة تحليلية للصور الشخصية، اعتمدت على عناصر محددة وهي الأوضاع والحركات الجسدية، تعبيرات الوجوه، الملابس والعمائم المزينة بالجواهر الثمينة، الأسلحة والسيوف المزينة بالجواهر الثمينة، والأثاث. وقد اختيرت ستة صور شخصية لملوك القاجار وتم تطبيق أسلوب التحليل الفني عليهم.
The art of painting regarded as one of the flourished arts in Islamic civilization. Islamic art was influenced to a large extent by the European culture and art during the Qajar period. The art of self-portrait during the Qajar reign rulers was confined to the royal court, due to Qajar’s rulers opining to the west, where artists of this age showed an increasing desire to accommodate the European arts to adapt the requirements of new beauty, where rulers took the portrait to confirm their new position and expressing their power and influence, both inside and outside the court, as well as being used as a tool with political objectives. Most of Qajar royal self-portraits were a reflection of Qajar’s society, their joys of life, in particular, their richness. The royal Qajar painters used over-adornment style in painting self-portrait, for example, cloth, furniture and weapons adorned with jewellery to show luxury. The current research took a different reading and analysis methodology based on specific criteria: movements and facial expressions in self-portrait, clothes and turbans adorned with jewels, weapons decorated with precious jewels in self-portrait. Six royal Qajar self-portrait paintings were chosen and artistic analysis applied on them.
Keywords: الفن الإسلامى -- الفنون التشكيلية -- التزيين التشكيلى -- ملوك القاجار